Imbalance of NET and Alpha-1-Antitrypsin in Tuberculosis Patients Is Related With Hyper Inflammation and Severe Lung Tissue Damage - de Melo, Mayla Gabryele Miranda; Mesquita, Eliene Denites Duarte; Oliveira, Martha M.; Silva-Monteiro, Caio da; Silveira, Anna K. A.; Malaquias, Thiago S.; Dutra, Tatiana C. P.; Galliez, Rafael M.; Kritski, Afrânio L.; Silva, Elisangela C.; , the Rede-TB Study Group (Frontiers in Immunology, 2019)
Background: Pulmonary tuberculosis (PTB) can lead to lung tissue damage (LTD) and compromise the pulmonary capacity of TB patients that evolve to severe PTB. The molecular mechanisms involved in LTD during anti-tuberculous treatment (ATT) remain poorly understood. Methods and findings: We evaluated the role of neutrophil extracellular trap (NET) and the occurrence of LTD through chest radiographic images, the microbial load in sputum, and inflammatory serum profile (IL-12p40/p70, IL-8, IL-17A, IL-23, VEGF-A, MMP-1 and -8, galectin-3, citrunillated histone H3 - cit-H3, alpha-1-antitrypsin - α1AT, C-reactive protein - CRP and albumin) in a cohort of 82 PTB patients before and after 60 days of ATT. Using univariate analysis, LTD was associated with neutrophilia and increase of several inflammatory proteins involved in the neutrophil-mediated response, being cit-H3 the more related to the event. In the multivariate analysis, neutrophilia and cit-H3 appear as directly related to LTD. The analysis of the ROC curve at day 60 presented AUC of 0.97 (95.0 % CI 0.95-1). Interestingly, at day 0 of ATT, these biomarkers demonstrated fine relation with LTD showing an AUC 0.92 (95.0 % CI 0.86- 0.99). Despite of that, the same molecules have no impact in culture conversion during ATT. Conclusions: our data revealed that NETs may play a key role in the pathway responsible for nonspecific inflammation and tissue destruction in PTB. High level of cit-H3 and low level of α1AT was observed in the serum of severe TB patients, suggesting a breakdown in the intrinsic control of NET-driven tissue damage. These data show a new insight to knowledge TB immunopathogenesis, the role of neutrophil and NET pathway. Likewise, we identified possible biomarkers to screening of PTB patients eligible to adjuvants therapies, as anti-inflammatories and alpha-1-antitrypsin.